Long-term effects of growth hormone on infarct size and left ventricular function in sheep with coronary artery occlusion - Olea, Fernanda Daniela (2010)
The effects of growth hormone (GH) on infarct size and left ventricular (LV) function in experimental acute myocardial infarction (AMI) have been controversial. Moreover, little, if any, information exists regarding long-term evaluation of therapeutic doses of GH in large mammalian models of AMI. We therefore aimed to assess the effect of therapeutic doses of GH over 3.5 months on infarct size and heart function in sheep with AMI. After coronary artery ligation, sheep received subcutaneous human GH 8 IU/d (n = 8) or vehicle (n = 8) over 100 days. Infarct area was similar in GH (16.9% 6 3% of LV area) and placebo (16.5% 6 3.7%, P = not significant) sheep. At 3 days of treatment onset, but not at later times, GH sheep had higher LV shortening fraction (30.7% 6 3.5% vs. 24.8% 6 6.1%, P , 0.04), systolic anterior wall thickness (10.1 6 0.8 vs. 8.6 6 1.2 mm, P , 0.02), and cardiac index (3.8 6 0.6 vs. 2.8 6 0.7 L min21 m22 , P , 0.01). This evolution of function parameters paralleled that of serum insulin-like growth factor 1 levels, which differed significantly only during the first week, suggesting a direct effect of GH on LV contractility. These results may suggest the usefulness of therapeutic doses of GH at the early phases of AMI but do not support maintaining the treatment for longer time.